(untitled) (Research, Society and Development, 2023)
Coalho cheese is one of the main products of the Brazilian Northeast, being formed through the coagulation of bovine milk using specific enzymes for this purpose. Most of the Coalho cheese production is artisanal, being produced in small and medium-sized companies. This leads to the production and commercialization of non-standard cheeses. Cheese is a product that undergoes a lot of manipulation, especially in small companies, which can contaminate the food, causing a risk to the health of the consumer. To prevent these risks, it is necessary to use GMP and HACCP programs in the production of Coalho cheese. This work aims to emphasize the importance of quality control in the manufacture of this dairy derivative, through a bibliographical review. A bibliographic survey was carried out on platforms such as Science Direct, Scielo, Google Scholar as well as books published in the area and websites specialized in the subject. The application of programs such as GMP and HACCP are essential to guarantee the quality of Coalho cheese, as in addition to following current legislation, it also instructs on hygiene conditions. Quality control also improves the Coalho cheese production system, offering a safe product for human consumption in terms of nutritional and microbiological standards.